Lateral Root Development in Potato Is Mediated by Stu-mi164 Regulation of NAC Transcription Factor - Zhang, Li; Yao, Lei; Zhang, Ning; Yang, Jiangwei; Zhu, Xi; Tang, Xun; Calderón-Urrea, Alejandro; Si, Huaijun (Frontiers in Plant Science, 2018)
The NAC designation is derived from petunia (Petunia hybrida) gene NO APICAL MERISTEM (NAM) and Arabidopsis genes ATAF1/ATAF2 and CUP-SHAPED COTYLEDON2 (CUC2), which belongs to the family of plant-specific transcription factors (TFs), and plays important role in plant development processes, such as response to biotic and abiotic stress, and hormone signaling. MicroRNAs (miRNAs) are a class of small, noncoding endogenous RNAs which play versatile and significant role in plant stress response and development via negatively affecting gene expression at a post-transcriptional level. Here we showed that Stu-mi164 had a complementary sequence in the CDS sequence of potato NAC TFs, and that NAC expression exhibited significant differences under osmotic stress. We measured expression levels of the Stu-mi164 target gene NAC262 between control and PEG treated plants using real time-PCR, and the results demonstrated that they had inverse relationship. We suggested that Stu-miR164 might drive overexpression of NAC gene under osmotic stress in potato. To confirm the regulation of NAC TFs by stu-mi164, we developed transgenic plants, using Agrobacterium tumefaciens mediated transformation, of the potato cultivars “Gannongshu 2” and “Kexin 3” overexpressing the stu-mi164 or the transcription factor NAC262. Real time-PCR analysis of transgenic potato plants under osmotic (PEG) stress, showed that potato plants overexpressing Stu-mi164 had reduced expression of NAC262 and their osmotic resistance decreased. Furthermore, these plants had low number of lateral roots although the same length as the control. Our findings support the regulatory role of Stu-miRNAs in controlling plant response to osmotic stress via NAC262.